EFEKTIVITAS PEMBELAJARAN MELALUI APLIKASI QUIZIZZ DI ERA PANDEMI PADA PEMBELAJARAN EKONOMI - Santoso, Tri Nugroho Budi; Destri Sambara Sitorus (Jurnal TEKNODIK, 2023)
This research is a continuation of previous research to test the effectiveness of the Quizizz application as a game-based learning media during the Covid-19 pandemic era. The approach used in this research is a mixed research method, type explanatory design, i.e. a combination of quantitative and qualitative data collection methods. The quantitative method uses the effectiveness test through a pair sample t-test, while the qualitative method uses SWOT analysis to describe the process of using educational game applications (Quizizz). The sampling technique used is cluster random sampling and data collection by observation, interviews, documentation, and questionnaires. Based on the output of the paired samples test, the sig value is known (2-tailed) as 0.000 < 0.05. So it can be concluded that there is an average difference between students' abilities in learning economics and accounting before and after using the Quizizz application. The SWOT analysis shows the strengths, which refer to its various features. While in terms of opportunities, it is more referring to the opportunity for the formation of learning communities. The challenge that must be solved is the internet network readiness of the participants.